IgE-mediated allergy to egg protein - Valdesoiro-Navarrete, Laura; Piquer Gibert, Monica; Molini Menchon, Natalia; Pinto-Fernández, Celia; García-Magán, Carlos; Claver-Monzón, Ángela; Thorndike-Piedra, Felipe; Blasco Valero, Cristina; Pereiro Fernández, Sara; Prieto-del-Prado, Ana; Ortega-Bernal, Gloria; Martorell Aragonés, Antonio (Allergologia et Immunopathologia, 2025)
Egg allergy is one of the most common food allergies in the pediatric population. It significantly impacts the quality of life of patients and their families. Egg allergy is an adverse reaction mediated by an immune mechanism. There are different mechanisms involved. This review refers to immunoglobulin E (IgE)-mediated egg allergy. The prevalence of egg sensitization and allergy is higher in children with cow’s milk allergy and in those with atopic dermatitis. The prognosis for egg allergy in young children is generally good, although in some cases it tends to persist at adult age. The main allergens in egg white are ovomucoid and ovalbumin. Diagnosis is based on the suggestive clinical history and the study of specific positive egg allergy. Oral food challenge test is the gold standard test to confirm diagnosis. Egg allergy, like other food allergies, is primarily managed with the avoidance diet and symptomatic treatment in case of an allergic reaction. The current approach emphasizes minimizing restrictive diets, if possible. Therefore, obtaining an accurate diagnosis through component-resolved diagnostics is essential, and whenever necessary, confirming tolerance through oral challenge tests. Food immunotherapy can be potentially curative and can be regarded as a therapeutic option for IgE-mediated egg allergy. It increases the amount of food tolerated and reduces the risk of a life-threatening anaphylactic reaction. There are different approaches: orally, sublingually, subcutaneous, or via epicutaneous. Among these, oral immunotherapy is the most extensively studied and widely used approach in clinical practice.